Routledge handbook of Asia in world politics - Chang, Teh-Kuang; Chang, Angelin (Routledge, Taylor & Francis Group, 2018)
Asia is a complex and diverse continent, which has seen the scope and pace of transformation increase rapidly over the past 30 years. In turn, the economic growth and social change seen in the region, combined with new global security profiles and environmental challenges, have contributed to placing Asia at the forefront of international affairs. The Routledge Handbook of Asia in World Politics will be useful to students and scholars of Global Politics, International Relations and Asian Studies.